Intelligent Traffic System: Cooperation of Manet and Image Processing - Badura, Stefan; Lieskovsky, Anton (Communications - Scientific letters of the University of Zilina, 2010)
This paper presents a model for intelligent traffic system. Proposed methods describe ideas of information computing from images and its distribution to different nodes in traffic system. Two algorithms for foreground extraction forwarded by classification of extracted objects are discussed in the paper.. These approaches serve as a basis for information computing. Communication framework over MANET is presented for efficient information delivery. Appropriate protocol is designed at first, and then some algorithms for efficient data delivery are discussed.